2021
DOI: 10.1016/j.toxrep.2021.03.009
|View full text |Cite
|
Sign up to set email alerts
|

"Metal elements and pesticides as risk factors for Parkinson's disease - A review"

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 208 publications
0
22
0
Order By: Relevance
“…Metal ions, especially heavy metals, are not easily metabolized and, therefore, accumulate in organs resulting in tissue damage and increasing disease vulnerability over time [ 129 , 130 ]. As a result, the accurate detection of metal ions in the environment or tissues is urgently needed as a prelude to environmental remediation [ 131 ] or clinical intervention strategies [ 28 , 132 ].…”
Section: Nanozymes and Their Potential Applications In Biosensingmentioning
confidence: 99%
“…Metal ions, especially heavy metals, are not easily metabolized and, therefore, accumulate in organs resulting in tissue damage and increasing disease vulnerability over time [ 129 , 130 ]. As a result, the accurate detection of metal ions in the environment or tissues is urgently needed as a prelude to environmental remediation [ 131 ] or clinical intervention strategies [ 28 , 132 ].…”
Section: Nanozymes and Their Potential Applications In Biosensingmentioning
confidence: 99%
“…But the complete series of steps leading to this cell death is still vague, and the underlying causes remain one of medicine’s greatest mysteries Worldwide occurrence. According to the 2016 Dorsey and GBD Collaborators Study—[ 212 ] published in 2018, 6·1 million (95% uncertainty interval [UI] 5·0 -7·3) individuals had Parkinson's disease globally, compared with 2·5 million (2·0—3·0) in 1990; Geographical variation ( cf ., latitude) plays key role in dementia risk (e.g., Russ et al—[ 52 ] High concentrations of Al and low levels of Mg observed in the pathogenesis of CNS (central nervous system) degeneration and PD—[ 213 ]; Association with metal and trace element concentration in urine, serum, whole blood and cerebrospinal fluid—[ 214 218 ]; Very high or very low levels of Se—[ 219 ] Combination of Mo deficiency and purine ingestion—[ 220 ] Significant association between the PD mortality rates and soil concentrations of Se, Sr, and Mg—[ 221 223 ]; Elevated trace metals (namely, Cu, Zn, Mg and Fe) found, compared to controls (ρ < 0.001) in Nigerian Parkinson’s Disease patients—[ 224 ] Existence of seasonality (related to temperature) in Parkinson's disease symptoms—[ 225 ]; Improvement of PD symptoms at high altitude—[ 226 , 227 ]; Several risk factors in development of PD at high altitude—[ 228 ] Regional maps depicting correlations between the distribution (clusters) of PD and soil geochemistry which would be helpful in this aetiological debate; but are very rare in the published literature (See an example in: Sun—[ 221 ] for PD distribution in the United States) To date, according to Ullah et al—[ 229 ], the fundamental molecular mechanisms of PD aetiology and pathogenesis remain unclear, with a number of epidemiological studies implicating metal toxicity in the diseases’ pathogenesis via several potential mechanisms. In many instances, the metal equilibrium is thought to be disturbed, leading to deleterious effect on the entire body including the brain 18.…”
Section: Introductionmentioning
confidence: 99%
“…To date, according to Ullah et al—[ 229 ], the fundamental molecular mechanisms of PD aetiology and pathogenesis remain unclear, with a number of epidemiological studies implicating metal toxicity in the diseases’ pathogenesis via several potential mechanisms. In many instances, the metal equilibrium is thought to be disturbed, leading to deleterious effect on the entire body including the brain…”
Section: Introductionmentioning
confidence: 99%
“…Mn accumulation in humans can cause central nervous system disorder. Fe is implicated in reactive oxygen species generation, causing cell dysfunction and finally cell death ( Ullah et al., 2021 ). Cr exerts carcinogenic effects through mutagenesis ( Wallace and Djordjevic, 2020 ).…”
Section: Introductionmentioning
confidence: 99%